Lange USMLE road map : - Gordon, Paul (McGraw-Hill, 2007)
Guideposts to understanding: Clinical Correlations: link a topic to its clinical application and illuminate the relationship between basic science and clinical practice; Clinical Problems: Build on the basic concepts and offer valuable practice for the USMLE and course examinations; Explanations of Answers Provide the "whys" to pinpoint your strengths and weaknesses.